Strategi pencegahan non-farmakologis pada rhinitis alergi dalam mengatasi keterbatasan terapi antihistamin jangka panjang: Systematic review - Iwan Setiawan Adji; Sabira Husna Ristyana; Noval Gentha Mahensa; Witrishya Anggrahini; Aisyah Nabilah; Marshanda Ariella Nadhifa; Lina Nur Fatimah; Dhia Laila Nadzifa (Jurnal Kesehatan Andalas, 2026)
Non-pharmacological prevention strategies for allergic rhinitis in addressing the limitations of long-term antihistamine therapy: A systematic review Antihistamine therapy in Allergic rhinitis is generally the primary choice for symptom management. However, long-term use often presents side effects such as sedation, tolerance, and lack of control over allergen exposure. Non-pharmacological preventive strategies are important to explore as complementary and alternative approaches. Objective: To analyze effective non-pharmacological strategies for the prevention of allergic rhinitis. Methods: A literature search was conducted across electronic databases such as PubMed, Scopus, and Google Scholar, focusing on publications published between 2015 and 2024. The selected studies included experimental studies, systematic reviews, and clinical guidelines addressing non-pharmacological interventions for allergic rhinitis. The most frequently discussed non-pharmacological strategies included environmental controls (e.g., reducing exposure to dust, mites, and air pollution), nasal saline irrigation, mask use, lifestyle modifications, and patient education. Results: Several interventions have shown significant reductions in symptom scores and improvements in patients' quality of life, especially when combined with pharmacological therapy. Non-pharmacological approaches have significant potential as long-term management strategies for allergic rhinitis. Conclusion: The combination of education, environmental modifications, and physical interventions can reduce symptom frequency and the need for antihistamines. Keywords: allergic rhinitis, antihistamines, environmental modifications, non-pharmacological, prevention